Handgrip strength and endurance of apparently healthy subjects - Gurung, Sanyukta; Bahadur Mahotra, Narayan; Shrestha, Lava; Laxmi Shakya, Yagya; Bhat, Neeti (Journal of Chitwan Medical College, 2025)
Introduction: Musculoskeletal fitness, strength and endurance can be measured by hand grip strength (HGS) and endurance (HGE). This study aimed to assess HGS and HGE according to sociodemographic and personal habits. Method: A cross-sectional descriptive study was conducted at Tribhuvan University Teaching Hospital from 2020 to 2022 among apparently healthy adults recruited by convenience sampling after ethical clearance. Bodybuilders, pregnant women, and those with a history of chronic illness were excluded. The HGS and HGE were measured by the Camry digital hand dynamometer. Age, gender, handedness, BMI, waist circumference, smoking, alcohol consumption and knuckle cracking habits were recorded. Data were checked for normality. Data were expressed descriptively using mean, frequency and percentage. Data were analysed with IBM SPSS v16.0. Result: A total of 440 participants (332 males, 108 females), mean age 32.4±8.0 years, were included. The HGS was higher in males with 40.76+6.44 kg than in females, 26.49+4.00 kg, whereas females showed longer HGE 139.5±61.8 than males 125.3±46.9 s. The HGS peaked in men aged 25–29 years and women aged 35–39 years, whereas HGE was longest in 45–49 years, with women maintaining endurance longer than men at each age category. Higher BMI was associated with greater HGS but shorter HGE. Non-smokers and non-alcohol consumers had longer endurance than their counterparts. Conclusion: Males had higher handgrip strength, and females had longer handgrip endurance. Higher BMI was associated with increased strength but reduced endurance. Non-alcohol consumers showed better endurance capacity.